1997
DOI: 10.1523/jneurosci.17-13-05004.1997
|View full text |Cite
|
Sign up to set email alerts
|

Stretch Hyperreflexia of Triceps Surae Muscles in the Conscious Cat after Dorsolateral Spinal Lesions

Abstract: Resistive force and electromyograms from triceps surae muscles were measured during dorsiflexion of both ankles of awake cats before and after interruption of one dorsolateral funiculus (DLF). DLF lesions produced ipsilateral increases in dynamic and static reflex force that persisted over 66 weeks. The increase in dynamic reflex force was velocity sensitive, as demonstrated by a greater effect for 60°/sec than for 10°/sec dorsiflexion. Also, the lesions increased dynamic force to a greater extent than static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 68 publications
(69 reference statements)
0
28
0
Order By: Relevance
“…Although Ashworth scale has not been utilized in an animal model, other clinical parameters such as muscle stretch re¯ex, ankle clonus have been used as a measurement method for spasticity. 20,21 Electrophysiologic parameters are objective but there is some controversy regarding the usefulness of these parameters in evaluating spasticity. Although both H/M ratio and F/M ratio have been reported to assess either the spinal segmental re¯ex or excitability of the anterior horn cells, 22,23 there are studies reporting that they were increased in subjects with decreased muscle stretch re¯ex.…”
Section: Discussionmentioning
confidence: 99%
“…Although Ashworth scale has not been utilized in an animal model, other clinical parameters such as muscle stretch re¯ex, ankle clonus have been used as a measurement method for spasticity. 20,21 Electrophysiologic parameters are objective but there is some controversy regarding the usefulness of these parameters in evaluating spasticity. Although both H/M ratio and F/M ratio have been reported to assess either the spinal segmental re¯ex or excitability of the anterior horn cells, 22,23 there are studies reporting that they were increased in subjects with decreased muscle stretch re¯ex.…”
Section: Discussionmentioning
confidence: 99%
“…Following spinal cord injury (SCI), spasticity is a common problem in both the nonveteran [30] and veteran [31] populations, but robust spasticity has been difficult to reproduce in animal models, such as the SCI cat [32][33][34] or rat [35][36][37]. Without complete spinal transections, animals recover most motor function, a situation not seen in humans, where even partial spinal lesions often lead to chronic spasticity [38].…”
Section: Animal Models For Spasticitymentioning
confidence: 99%
“…However, in humans and in some animal models, considerable neuromuscular activity sometimes develops after SCI in the form of spasticity, a syndrome that includes hyperreflexia, hypertonus, and long-lasting spasms (Bennett et al 2004;Fujimori et al 1968;Heckman 1994;Kuhn and Macht 1948;Lance and Burke 1974;Ritz et al 1992;Taylor et al 1997). Furthermore, preservation of slow (Hidler et al 2002;Thomas and Ross 1997;Zijdewind and Thomas 2003) and fatigue-resistant (Hartkopp et al 2003) muscle contractile properties has been observed in conjunction with spasticity after SCI in humans.…”
Section: Introductionmentioning
confidence: 99%